2017
DOI: 10.2147/ott.s145105
|View full text |Cite
|
Sign up to set email alerts
|

Amatuximab and novel agents targeting mesothelin for solid tumors

Abstract: Mesothelin (MSLN) is considered a promising target for cancer therapy. Originally extracted in 1992 after the immunization of mice with a human ovarian cancer (OC) cell line and cloned in 1996, MSLN seems to be involved in cell adhesion and metastasis. MSLN is prevalent in mesothelia tissues but is expressed in several human cancers, such as OC, pancreatic cancer, mesothelioma, and lung cancer. Amatuximab (MORAb-009) is a mouse-human chimeric monoclonal antibody with a selective affinity for MSLN. The principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…54,55 A number of different MSLN-targeted therapies, including MSLNtargeting antibodies, antibody-drug conjugates, immunotoxins, and chimeric antigen receptor T cells, have been either clinically tested or are currently in early clinical development. 56 Using the anti-MSLN antibody anetumab (BAY 86-1903), a MSLN-targeted 227 Th conjugate (MSLN-TTC) was developed. 36 MSLN-TTC showed strong activity in several in vitro and in vivo preclinical models.…”
Section: Mesothelin-ttcmentioning
confidence: 99%
“…54,55 A number of different MSLN-targeted therapies, including MSLNtargeting antibodies, antibody-drug conjugates, immunotoxins, and chimeric antigen receptor T cells, have been either clinically tested or are currently in early clinical development. 56 Using the anti-MSLN antibody anetumab (BAY 86-1903), a MSLN-targeted 227 Th conjugate (MSLN-TTC) was developed. 36 MSLN-TTC showed strong activity in several in vitro and in vivo preclinical models.…”
Section: Mesothelin-ttcmentioning
confidence: 99%
“…[46][47][48][49][50] Many clinical trials and experimental therapies have targeted these two tumor markers, including vaccine, CA125/MUC16-or mesothelin-specific antibody and CAR T cell therapy. [51][52][53][54][55][56] Therefore, with these markers highly expressed in our model, this novel system physically recapitulates human HGSC development and spread, allowing for the preclinical screening of new therapies targeting CA125, mesothelin and many other markers.…”
Section: Discussionmentioning
confidence: 98%
“…The present results demonstrated that mesothelin, IGFBP2 and PP14 had potential value for diagnosing PROM. Mesothelin is a 40-kDa membrane-glycoprotein; it is reported to associate with a number of types of cancer, although, its biological function in normal conditions is unclear ( 15 ). IGFBP2 is a 36-kDa protein, which is primarily involved in metabolic disease and cancer ( 16 ).…”
Section: Discussionmentioning
confidence: 99%